1960
DOI: 10.1111/j.1748-1716.1960.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Connections and Functions of Muscle Nerves in the Kitten

Abstract: In this paper the postnatal development of the afferent terminals of muscle nerves is studied by means of the two‐neuron arc, in kittens from birth to 45 days. The experimental findings support earlier histological evidence for a postnatal development of the dorsal root collaterals of muscle nerves. Evidence is also presented that the afferent terminals in the newborn and young animals have properties different from those in the adult animal. Facilitation is found to be lacking in the newborn animal while inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1962
1962
1988
1988

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Thus, although analysis of evoked potential and single-unit activities show that neurones in the middle layers of the cortex may respond 758 RAT CEREBRAL NEURONE DEVELOPMENT synaptically to thalamic and peripheral stimulation as early as day P3 (Verley & Axelrad, 1975;Verley, 1977), it appears that the neurones of newborn cerebral cortex are constrained to a large extent in the frequency of their discharges by the presence of immature and poorly developed synaptic connections. Although failure of synaptic interactions has been previously ascribed to 'immaturity' of the anatomical synaptic apparatus (Skoglund, 1960;Prince & Gutnick, 1972), it is conceivable that the lower densities of Na+ and Ca2+ channels in immature cells suggested from our data and those of patch clamp recordings (Huguenard et al 1986;Hamill et al 1986) might have a more striking functional effect in the axonal terminal region where small alterations in inward currents might produce large effects on depolarization in terminals and consequent transmitter release. Further investigations of the development of electrophysiological synaptic characteristics of cortex neurones may allow a more complex explanation of the special characteristics of normal activities in immature neocortex and those which occur during abnormal states such as epileptogenesis.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, although analysis of evoked potential and single-unit activities show that neurones in the middle layers of the cortex may respond 758 RAT CEREBRAL NEURONE DEVELOPMENT synaptically to thalamic and peripheral stimulation as early as day P3 (Verley & Axelrad, 1975;Verley, 1977), it appears that the neurones of newborn cerebral cortex are constrained to a large extent in the frequency of their discharges by the presence of immature and poorly developed synaptic connections. Although failure of synaptic interactions has been previously ascribed to 'immaturity' of the anatomical synaptic apparatus (Skoglund, 1960;Prince & Gutnick, 1972), it is conceivable that the lower densities of Na+ and Ca2+ channels in immature cells suggested from our data and those of patch clamp recordings (Huguenard et al 1986;Hamill et al 1986) might have a more striking functional effect in the axonal terminal region where small alterations in inward currents might produce large effects on depolarization in terminals and consequent transmitter release. Further investigations of the development of electrophysiological synaptic characteristics of cortex neurones may allow a more complex explanation of the special characteristics of normal activities in immature neocortex and those which occur during abnormal states such as epileptogenesis.…”
Section: Discussionmentioning
confidence: 62%
“…2 B, C) cannot be attributed to the long refractory period of the presynaptic terminals of the afferent fibres (cf. Skoglund, 1960a). Inhibition, either Group Ib (Laporte & Lloyd, 1952;Eccles, Eccles & Lundberg, 1957b) or recurrent (Renshaw, 1946;Eccles, Fatt & Koketsu, 1954;Skoglund, 1960a), could be invoked to account for an apparent lack of facilitation.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of the monosynaptic reflex pathway in kittens Skoglund (1960) found that conditioning volleys in flexor nerves inhibited extensor reflexes with testing intervals up to 600 msec. Although a comparable inhibition of the monosynaptic reflexes of flexors was not seen when conditioned by flexors, this prolonged inhibition seems likely to be another example of presynaptic inhibition.…”
Section: Resultsmentioning
confidence: 99%